Organisational commitment and intention to stay in a telecommunication company - Ngo Ndjama, Joelle Danielle; Van Der Westhuizen, J. (International journal of research in business and social science, 2024)
Since today’s market is highly competitive and constantly evolving, organisations are striving to achieve high levels of productivity and low levels of turnover. One of the key factors in achieving this goal is organisational commitment. Thus, the study advocates that the level of employee commitment and willingness to continue working with the organisation is reflected in their intention to stay. Based on the theory of reasoned action, this study aims to investigate how the dimensions of employee commitment influence their decision to stay with the organisation in the long term within a telecommunication company. The study adopted a postpositivist perspective, a descriptive approach, a quantitative research method and a structured questionnaire to collect numerical data. In addition, descriptive, factor, correlation and regression analyses were performed through SPSS version 26.0. The study population consisted of 470 employees working in different departments, ranging from entry-level positions to consulting engineers. A sample of 298 employees was selected through a simple random sampling to minimise bias. Regression results indicated a moderate positive relationship between organisational commitment and intention to stay. The study recommends organisations to prioritise strategies that promote and sustain organisational commitment for improved intention-to-stay outcomes. This can be achieved through various means such as providing opportunities for professional development, recognising and rewarding employee contributions, and promoting open communication.